Psychological reactance to system-level policies before and after their implementation - Armin Granulo; Christoph Fuchs; Robert Böhm (Proceedings of the National Academy of Sciences, 2025)
Governments need to develop and implement effective policies to address pressing societal problems of our time, such as climate change and global pandemics. While some policies focus on changing individual thoughts and behaviors (e.g., informational interventions, behavioral nudges), others involve systemic changes (e.g., car bans, vaccination mandates). Policymakers may use system-level policies to achieve socially desirable outcomes, yet often refrain from doing so because they anticipate public opposition. In this article, we propose that people’s psychological reactance driving this opposition is a transient phenomenon that dissipates once system-level policies are in place. Using secondary survey data ( N = 49,674) and experimental data (six studies; N = 4,629; all preregistered), we document that psychological reactance to system-level policies is greater when they are planned (ex ante implementation) than when they are already implemented (ex post implementation). We further demonstrate that this effect can be observed across various intervention contexts and provide insights into its underlying psychological mechanisms. Specifically, ex ante vs. ex post the system-level policy’s implementation, individuals focus more on the transition-induced personal losses than on the prospective societal outcome gains. In line with this perspective, we show that the decline in reactance to system-level policies after their implementation is mediated and moderated by the salience of personal losses, and that the initial reactance to such policies is mitigated by the salience of societal gains. These findings suggest that the public’s negative reactions to system-level policies are more transient than previously thought and can help policymakers design effective interventions.